Iron phosphate mediated magnetite synthesis: a bioinspired approach. Issue 27 (21st June 2021) - Mirabello, Giulia; GoodSmith, Matthew; Bomans, Paul H. H.; Stegbauer, Linus; Joester, Derk; de With, Gijsbertus
Abstract : Magnetite was synthesized from a mixed valence iron phosphate precursor through a novel mechanism inspired by biomineralization in magnetotactic bacteria. Abstract : The biomineralization of intracellular magnetite in magnetotactic bacteria (MTB) is an area of active investigation. Previous work has provided evidence that magnetite biomineralization begins with the formation of an amorphous phosphate-rich ferric hydroxide precursor phase followed by the eventual formation of magnetite within specialized vesicles (magnetosomes) through redox chemical reactions. Although important progress has been made in elucidating the different steps and possible precursor phases involved in the biomineralization process, many questions still remain. Here, we present a novel in vitro method to form magnetite directly from a mixed valence iron phosphate precursor, without the involvement of other known iron hydroxide precursors such as ferrihydrite. Our results corroborate the idea that phosphate containing phases likely play an iron storage role during magnetite biomineralization. Further, our results help elucidate the influence of phosphate ions on iron chemistry in groundwater and wastewater treatment.